2020
DOI: 10.1016/j.heliyon.2020.e03962
|View full text |Cite
|
Sign up to set email alerts
|

In vivo and in silico evaluation of antinociceptive activities of seed extract from the Holarrhena antidysenterica plant

Abstract: The objective of the study was to investigate the analgesic activity of seeds extracted from the Holarrhena antidysenterica plant (Family: Apocynaceae). The seeds of H. antidysenterica were extracted with pure ethanol and administered to the experimental Swiss albino mice at three different doses (50, 100, and 150 mg/kg body weight) in pain models. Peripheral analgesic activity was evaluated using the acetic acid-induced writhing test, and heat-induced (hot plate and tail immersion test) pain models were appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 39 publications
2
6
0
Order By: Relevance
“…Any agent that reduces the number of licking responses will reveal analgesia in animal by inhibition of prostaglandin synthesis, a peripheral mechanism of pain inhibition. 29 During formalin test, the chloroform fractions at 500 mg/kg body weight showed maximum analgesic activity with 35.44% inhibition of licking responses induced by formalin, whereas aspirin at a dose of 10 mg/kg body weight exhibited 53.22% inhibition. Our observed result showed that the analgesic effect of L. spinosa is too peripherally mediated.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Any agent that reduces the number of licking responses will reveal analgesia in animal by inhibition of prostaglandin synthesis, a peripheral mechanism of pain inhibition. 29 During formalin test, the chloroform fractions at 500 mg/kg body weight showed maximum analgesic activity with 35.44% inhibition of licking responses induced by formalin, whereas aspirin at a dose of 10 mg/kg body weight exhibited 53.22% inhibition. Our observed result showed that the analgesic effect of L. spinosa is too peripherally mediated.…”
Section: Resultsmentioning
confidence: 94%
“…Time taken by the mouse to withdraw the tail is termed as tail immersion time. 29 Centrally acting analgesics elongate this responding time. In our study, the control group showed faster tail flicks at different time intervals of the experiment (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…Many plant extracts and isolated compounds from these have been proved to be analgesic by evaluating through models reported for analgesic activity (Bhuiyan et al, 2020). Crude alkaloidal fractions from medicinal plants are reported to possess analgesic response (Shoaib et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The hot plate is a standard method for evaluating central analgesic activity in animal models that use thermal stimuli as pain inducers with temperature was maintained at 55°C. The principle of this method is a change in spinal cord level, which effectively describes the centrally mediated anti-nociceptive response 24 . The paw-licking or jumping are defined as pain reflex behavior [25][26][27] .…”
Section: Analgesic Activity With Hot Plate Testmentioning
confidence: 99%